Disparities in physician compensation for breast and prostate cancer operations - Noah Khosrowzadeh; Aren Singh Saini; Kayla Samimi; Kyle Chambers; Matthew Gompels; Cristiane Takita; Jessica Meshman; Cyrus Washington (PLoS ONE, 2025)
The objective of this study was to determine whether the Center for Medicare and Medicaid services (CMS) pays more relative value units (RVUs) for prostatectomies than mastectomies across different treatment modalities. The RVU model is public information, subject to review every 5 years at minimum and has implications directly or indirectly to every medical center in the United States. These findings shed light on how the CMS values the two most prominent cancers among men and women: breast cancer and prostate cancer. An economic evaluation was conducted to appraise physician compensation for treating breast cancer vs prostate cancer. Work RVUs, malpractice RVUs, and practice expense RVUs were collected from the CMS’ 2023 Physician Fee Scheduler. The total operative times, including time spent in pre-op consultations and follow ups, used by the RVU update committee to create these values were collected from the CMS’ 2023 Final Rule Physician Work Times. Surgical oncologists treating breast cancer were paid an average of 15.45 RVUs per mastectomy and 2.74 per hour. The average work RVUs paid for a prostatectomy was 24.64 and 3.06 per hour. The average work RVUs paid for an axillary lymph node removal was 12.29 and 2.94 per hour. The average work RVUs paid for a pelvic lymphadenectomy was 15.87 and 3.04 per hour. The data assimilated in this study acts to illustrate the discrepancy between work RVUs for breast cancer and prostate cancer operations.